Clinical validation of two immunochromatographic SARS-CoV-2 antigen tests in near hospital facilities - Skvarč, Miha (The Journal of Infection in Developing Countries, 2022)
Introduction: Rapid antigen tests to detect SARS-CoV-2 virus need to be validated. The purpose of clinical validation is to place the test into the everyday working process in health care institutions. Methodology: The clinical validation of Alltest Covid19 antigen test (Alltest, China) and Vivadiag Pro SARS- CoV-2 antigen tests (Vivacheck, China) started in four Slovenian health care institutions in December as a point-of-care test. Institutions compared the results of antigen tests to Seegene Allplex™ 2019-nCoV rt-PCR assay (SeeGene, South Korea) and Cobas 6800 SARS CoV-2 rt-PCR (Roche, USA). Results: Sensitivity (90.6%, 95% CI = 84.94%-94.36%) and specificity (100%, 95% CI = 99.41%-100%) of Vivadiag Pro SARS CoV-2 Ag test were observed. While validating Alltest Covid19 Ag assay we got similar results (sensitivity 94.37%, 95% CI = 89.20% – 97.54%), specificity 100% (95% CI = 98.83% - 100%). Conclusions: Vivadiag Pro SARS CoV-2 Ag test and Alltest Covid19 test proved to be a good screening tool to detect SARS-CoV-2. The accurate information about the patient’s status was available almost immediately and there was no need to wait for rt-PCR results. We could prevent further spread of the SARS-CoV-2 in primary care and hospital settings.